2016
DOI: 10.3233/cbm-160621
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pre-operative serum uric acid levels in esophageal squamous cell carcinoma patients who undergo R0 esophagectomy

Abstract: The pre-operative level of SUA is an independent prognostic predictor in ESCC patients who undergo R0 esophagectomy and patients with higher SUA level may have an unfavorable survival probability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…[15] Serum UA level has been considered as an independent predictor of the prognosis in some cancer such as esophageal squamous cell carcinoma, nasopharyngeal carcinoma, and oral squamous cell carcinoma. [1618] In addition, higher serum UA concentrations have been observed in cancer patients since nucleic acid turnover in proliferating diseased tissue. [19] Indeed, serum UA concentrations have been demonstrated to be related to inflammation and oxidative stress in some non-neoplastic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Serum UA level has been considered as an independent predictor of the prognosis in some cancer such as esophageal squamous cell carcinoma, nasopharyngeal carcinoma, and oral squamous cell carcinoma. [1618] In addition, higher serum UA concentrations have been observed in cancer patients since nucleic acid turnover in proliferating diseased tissue. [19] Indeed, serum UA concentrations have been demonstrated to be related to inflammation and oxidative stress in some non-neoplastic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…An addition of parameters, especially easy and cheap determinable parameters, may help to better classify those patient subgroups. Uric acid that is routinely measured since many years without any additional laborious effort has been proven to have prognostic utility in various solid cancers (Szkandera et al , 2014; Stotz et al , 2014; Yan et al , 2015; Chen et al , 2016). Regardless of the type of solid cancer, these studies showed that elevated pretreatment uric acid levels have a negative impact on PFS and OS of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore patients with solid cancers or haematological malignancies often present with high levels of uric acid in the blood. Importantly, a number of studies have demonstrated that elevated uric acid levels both increases the risk of cancer incidence and mortality, and correlate with a poor prognosis in several types of solid cancer, including pancreatic cancer, oesophageal cancer and colon cancer (Stotz et al , 2014; Yan et al , 2015; Chen et al , 2016). To our knowledge the exact role of uric acid level for prognostic risk stratification in DLBCL has not been established.…”
mentioning
confidence: 99%
“…For nasopharyngeal cancer, low post-treatment plasma uric acid levels may be better for patients who benefit from additional aggressive treatment after intensity-modulated radiotherapy, implicating low SUA as possibly conducive to cancer therapy [21]. Evidence has shown that preoperative SUA is an independent prognostic predictor in esophageal squamous cell carcinoma patients who undergo R0 esophagectomy, and patients with a higher SUA level might have significantly shorter 1, 3, and 5 year survival times than patients with a relatively low SUA level [22]. For colorectal cancer (CRC), it was found that SUA levels gradually increased from stage I to stage IV, suggesting that the SUA level reflected the severity of CRC and may help to evaluate the therapy effect as well as the prognoses of CRC patients [14].…”
Section: Uric Acid As a Risk Factor In Various Cancersmentioning
confidence: 99%